Colchicine modulates expression of pro-inflammatory genes in neutrophils from patients with familial Mediterranean fever and healthy subjects - Manukyan, G; Petrek, M; Tománková, Tereza; Martirosyan, A; Tatyan, M; Navratilova, Z; Paulu, D; Kriegova, E (Journal of Biological Regulators & Homeostatic Agents, 2013)
Colchicine (Col) is a microtubule depolymerizing drug, widely used for treatment of familial Mediterranean fever (FMF). Mechanisms by which Col exerts its beneficial effects are not yet completely understood, especially with respect to gene expression in polymorphonuclear neutrophils (PMNs), the main effector cells in acute inflammatory attacks of FMF. This study was, therefore, designed to elucidate possible modulatory effect of Col on expression of inflammation-related genes in circulating PMNs from 16 FMF patients in the remission period and 11 healthy subjects. In vitro effect of Col exposure (1 microg/ml) on expression of 8 selected genes was examined using quantitative real-time RT-PCR. Col up-regulated expression of IL-8 and IL-1beta genes in FMF (13-fold and 2.7-fold, p less than 0.05, respectively) and healthy (3-fold and 6.5-fold, p less than 0.05, respectively) PMNs, and down-regulated caspase-1 in FMF neutrophils (3-fold, p less than 0.05). In FMF PMNs treated with Col mRNAs of IL-8 (51-fold, p less than 0.01) and c-FOS (7-fold, p less than 0.05) transcripts were elevated compared to those from healthy subjects. By contrast, caspase-1 mRNA was decreased in FMF neutrophils compared to healthy cells (1.6-fold, p less than 0.05). Hereby, we provide evidence that, at least in vitro, Col displays pro-inflammatory potential in respect to IL-1beta and IL-8 genes. At the same time, our findings implicate suppression of caspase-1 expression by Col as a potential mechanism for its effects in FMF treatment.
Keywords: dospělí; Female; kolchicin; Interleukin-8; Familial Mediterranean Fever; Adult; Colchicine; ženské pohlaví; Adolescent; lidé; familiární středomořská horečka; kaspasa 1; regulace genové exprese; interleukin-8; Interleukin-1beta; Male; Caspase 1; Neutrophils; neutrofily; interleukin-1beta; Gene Expression Regulation; mužské pohlaví; mladiství; Humans